Synthesis and Characterization of Host Guest Inclusion Complexes of Cyclodextrin Molecules with Theophylline by Diverse Methodologies - Dutta, Ashutosh; Roy, Niloy; Das, Koyeli; Roy, Debadrita; Ghosh, Raja; Roy, Mahendra Nath (Emerging Science Journal, 2020)
Steady host–guest inclusion complexes have been produced with medicinally important guest molecule theophylline within aqueous α-Cyclodextrin and HP-β-Cyclodextrin. α-and HP-β-Cyclodextrins have been established with favorable structural features for inclusion with Theophylline which include diversified applications in modern science such as controlled delivery in the field of pharmaceuticals, food processing, pesticides, foodstuffs etc. Theophylline is one of the most widely accepted drugs for the treatment of asthma and chronic obstructive pulmonary disease (COPD) worldwide, even if it has been used clinically for many years. With both α and HP-β-Cyclodextrins it is found that 1:1 hosts-guest inclusion complexes are formed with the guest molecule theophylline. The construction and quality of the inclusion complexes have been characterized by using conductivity measurement, surface tension study, and Job’s method. The inclusion phenomenon has been confirmed by FTIR spectroscopy, proton NMR study. Association constants and thermodynamic parameters have been evaluated for the created inclusion complexes by ultraviolet spectroscopy.